2010
DOI: 10.1186/1756-8935-3-9
|View full text |Cite|
|
Sign up to set email alerts
|

HP1γ function is required for male germ cell survival and spermatogenesis

Abstract: BackgroundHP1 proteins are conserved components of eukaryotic constitutive heterochromatin. In mammals, there are three genes that encode HP1-like proteins, termed HP1α, HP1β and HP1γ, which have a high degree of homology This paper describes for the first time, to our knowledge, the physiological function of HP1γ using a gene-targeted mouse.ResultsWhile targeting the Cbx3 gene (encoding the HP1γ protein) with a conditional targeting vector, we generated a hypomorphic allele (Cbx3hypo), which resulted in much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…In biochemical assays HP1 isotypes are interchangeable and can form heterodimers (Nielsen et al 2001). Despite this they are not functionally redundant as evidenced by their different mutant phenotypes (Aucott et al 2008;Brown et al 2010;Singh 2010). Immuno-localization studies have shown that HP1α and HP1β are enriched within constitutive heterochromatin, while HP1γ has a more euchromatic distribution (Minc et al 1999).…”
Section: Mammalian Hp1 Proteins and Heterochromatin-like Complexesmentioning
confidence: 99%
“…In biochemical assays HP1 isotypes are interchangeable and can form heterodimers (Nielsen et al 2001). Despite this they are not functionally redundant as evidenced by their different mutant phenotypes (Aucott et al 2008;Brown et al 2010;Singh 2010). Immuno-localization studies have shown that HP1α and HP1β are enriched within constitutive heterochromatin, while HP1γ has a more euchromatic distribution (Minc et al 1999).…”
Section: Mammalian Hp1 Proteins and Heterochromatin-like Complexesmentioning
confidence: 99%
“…15 More specifically, Cbx3 has been documented to negatively regulate adipocyte differentiation from preadipocyte cells and is required for male germ cell survival and spermatogenesis. 16 Another study also suggested Cbx3 plays an important role in the epigenetic regulation of both cell differentiation and cancer development. 17 However, little is known about the functional involvement of Cbx3 protein in SMC differentiation from stem/progenitor cells and cardiovascular system development.…”
mentioning
confidence: 99%
“…9 Similarly, knockout of CBX5, the gene that encodes for HP1a has no apparent phenotype. 10,11 Consistent with these phenotypes, WRN-/-mice, unlike humans, have no phenotype. 12 But given the results of Zhang et al in human MSC's, a Werner's syndrome-like phenotype might have been expected for both SUV39H1 and CBX5 null mutants.…”
Section: Introductionmentioning
confidence: 54%